Development of methods for spawning, fertilization, larval husbandry, and settlement in the temperate coral Astrangia poculata - E. M. Borbee; I. Changsut; J. S. McAlister; T. Demarco; S. W. Davies; C. F. Ianniello; M. Sánchez García; L. M. Roberson; A. Schickle; J. M. Sneed; G. Pelose; D. Wuitchik; et al. (Frontiers in Marine Science, 2026)
The temperate coral Astrangia poculata has recently emerged as a useful experimental organism for studying symbiosis, organism-environment interactions, and embryonic development. Crucial to the success of establishing any species as a laboratory animal are reliable husbandry protocols and the ability to culture the full life cycle in captivity. Here, we detail efforts resulting from several years (2016-2025) of collaboration by a multi-institutional group of researchers toward standardized and reproducible methods for A. poculata spawning, fertilization, larval husbandry, and settlement in the laboratory. Spawning in A. poculata can be reliably induced in the laboratory via thermal treatment, and the methods presented here yielded laboratory fertilization rates of up to 93%. Unfed larvae exhibit rates of development comparable to previous reports, and larvae supplemented with commercially available organic matter sources, including Reef Roids and Reef Snow, exhibited signs of accelerated development. Settlement (attachment and metamorphosis) of A. poculata larvae was achieved using tetrabromopyrrole (TBP), a small molecule previously shown to induce settlement and/or metamorphosis in several tropical coral species. The methods described here, including augmentation of A. poculata larval culture with feed, and TBP-triggered settlement, represent a necessary first step for culturing A. poculata individuals throughout the life cycle, which can be scaled and adapted to enable new lines of inquiry dependent on experimental manipulation of specific genetic host lineages, and/or early life stages.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Anticoagulant rodenticide exposure in common buzzards: Impact of new rules for rodenticide use - Sheila George; E. Sharp; S. Campbell; A. Giela; C. Senior; L.M. Melton; D. Vyas; L. Mocogni; M. Galloway (Science of The Total Environment, 2024)

Conservation genomics of an exploited, popular aquarium trade species: the giant Caribbean sea anemone Condylactis gigantea (Anthozoa: Actiniidae) - Nancy E. Sheridan; Seifu Seyoum; William C. Sharp; Benjamin M. Titus; Marymegan Daly; Christina L. Richards; Aaron W. Schrey (Conservation Genetics, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Vegetation Cover, Tidal Amplitude and Land Area Predict Short-Term Marsh Vulnerability in Coastal Louisiana - Donald R. Schoolmaster; Camille L. Stagg; Leigh Anne Sharp; Tommy E. McGinnis; Bernard Wood; Sarai C. Piazza (Ecosystems, 2018)

Growth, survival, and competitive ability of chestnut (Castanea Mill.) seedlings planted across a gradient of light levels - Cornelia C. Pinchot; Scott E. Schlarbaum; Stacy L. Clark; Arnold M. Saxton; Ami M. Sharp; Callie J. Schweitzer; Frederick V. Hebard (New Forests, 2017)

Critical Review on the Public Health Impact of Norovirus Contamination in Shellfish and the Environment: A UK Perspective - Francis Hassard; Jasmine H. Sharp; Helen Taft; Lewis LeVay; John P. Harris; James E. McDonald; Karen Tuson; James Wilson; David L. Jones; Shelagh K. Malham (Food and Environmental Virology, 2017)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Monitoring agricultural rodenticide use and secondary exposure of raptors in Scotland - J. Hughes; E. Sharp; M. J. Taylor; L. Melton; G. Hartley (Ecotoxicology, 2013)

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Deep Autotrophic Soil Respiration in Shrubland and Woodland Ecosystems in Central New Mexico - D. O. Breecker; L. D. McFadden; Z. D. Sharp; M. Martinez; M. E. Litvak (Ecosystems, 2012)

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Impact of PSA testing and prostatic biopsy on cancer incidence and mortality: comparative study between the Republic of Ireland and Northern Ireland - A-E. Carsin; F. J. Drummond; A. Black; P. J. van Leeuwen; L. Sharp; L. J. Murray; D. Connolly; L. Egevad; M. Boniol; P. Autier; H. Comber; A. Gavin (Cancer Causes & Control, 2010)

Increasing CNS Noradrenaline Reduces EAE Severity - Maria Vittoria Simonini; Paul E. Polak; Anthony Sharp; Susan McGuire; Elena Galea; Douglas L. Feinstein (Journal of Neuroimmune Pharmacology, 2010)

Kinetic Modeling of Contrast-Enhanced MRI: An Automated Technique for Assessing Inflammation in the Rheumatoid Arthritis Wrist - Matthew L. Zierhut; Jill C. Gardner; Mary E. Spilker; John T. Sharp; Paolo Vicini (Annals of Biomedical Engineering, 2007)

Enhancement of dopamine-mediated behaviour by the NMDA antagonists MK-801 and CPP: similarities with repeated electroconvulsive shock - S. E. Smith; L. Acton; T. Sharp (Psychopharmacology, 1997)